Students’ Perception of Teachers Nonverbal Immediacy Behavior toward Students’ Attitude and Motivation in Learning English - Rendra Kusuma Wijaya (ELT Worldwide: Journal of English Language Teaching, 2017)
The objectives of the research were to provide information about students’ perception of teachers’ nonverbal immediacy behavior toward students’ attitude and motivation in learning English. This research is descriptive by nature employing mixed method QUAN-qual model. Participants of this research were the students of X IIS 2 and XI MIA 4 who were taught by male and female teacher. The data were obtained from questionnaire, group interview, and observation. The data from questionnaire were analyzed by using simple descriptive statistic and the data from interview and observation were analyzed by using interactive model of data analysis procedure consisting data collection, data reduction, and data display, and conclusion drawing. The finding showed that the mean score of students’ attitude was 76.56 under category positive attitude. The mean score of students’ motivation was 75.43 under category motivated. The students perceived that teachers’ nonverbal immediacy behavior influenced their attitude and motivation positively or negatively depending on particularr determinant factors such as religion, culture, and age. The findings led to the onclusion that managing nonverbal immediacy behaviors was very important for teachers because the behaviors could help changing students’ attitude from negative attitude became positive attitude and changing students motivation from demotivated became motivated during learning process in the class.Key words: Nonverbal immediacy behavior, attitude, motivation